2015
DOI: 10.1016/j.mric.2015.05.004
|View full text |Cite
|
Sign up to set email alerts
|

Magnetic Resonance Imaging–Guided Breast Interventions

Abstract: Synopsis Contrast enhanced breast MRI is increasingly being used to diagnose breast cancer and to perform biopsy procedures. The American Cancer Society has advised women at high risk for breast cancer to have breast MRI screening as an adjunct to screening mammography. This article places special emphasis on biopsy and operative planning involving MRI and reviews utility of breast MRI in monitoring response to neoadjuvant chemotherapy. We describe peer-reviewed data on currently accepted MR-guided therapeutic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 89 publications
(92 reference statements)
0
2
0
Order By: Relevance
“…In addition, DSA belongs to invasive examinations, which are difficult to accept in some patients. DCE-MRI vessel MIP 3D reconstruction technique can not only clearly show the blood supply of the breast lesion, but also intuitively show the 3D stereo relationship between the blood supply vessel and the lesion, which is convenient to find the tumor feeding artery and its microcirculation characteristics and has important implications for the diagnosis and differential diagnosis of breast lesions (22)(23)(24).…”
Section: Discussionmentioning
confidence: 99%
“…In addition, DSA belongs to invasive examinations, which are difficult to accept in some patients. DCE-MRI vessel MIP 3D reconstruction technique can not only clearly show the blood supply of the breast lesion, but also intuitively show the 3D stereo relationship between the blood supply vessel and the lesion, which is convenient to find the tumor feeding artery and its microcirculation characteristics and has important implications for the diagnosis and differential diagnosis of breast lesions (22)(23)(24).…”
Section: Discussionmentioning
confidence: 99%
“…Lee JM et al [51] reported an 8% to 13% cancellation rate of the procedure. Non-visualization of the suspicious finding may be due to change in tissue enhancement as the patient is in a different phase of her period or may be related to compression of breast tissue with decreased inflow of contrast material [52].…”
Section: Challenging Clinical Situationsmentioning
confidence: 99%